An observational study identifying obese subgroups among older adults at increased risk of mobility disability: do perceptions of the neighborhood environment matter?. - King, Abby C.; Salvo, Deborah.; Banda, Jorge A.; Ahn, David K.; Gill, Thomas M.; Miller, Michael.; Newman, Anne B.; Fielding, Roger A.; Siordia, Carlos.; Moore, Spencer.; Folta, Sara.; Spring, Bonnie.; Manini, Todd.; Pahor, Marco. (2016)
Background: Obesity is an increasingly prevalent condition among older adults, yet relatively little is known about how built environment variables may be associated with obesity in older age groups. This is particularly the case for more vulnerable older adults already showing functional limitations associated with subsequent disability.; Keywords: Obesity, Aging, Perceived environment, Neighborhood, Mobility, Disability, Residential density, Race/ethnicity, Homophily, Recursive partitioning.; Springer Open.